SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KELAYAKAN USAHA MANUFAKTUR DITINJAU DARI ASPEK KEUANGAN - Kusumawati Yupie (Semantik, 2011)
For investors or companies that will expand, business feasibility assessment is an image of business will be done so it can be seen the possibility - the possibility of benefits to be received. In connection with this we need an approach that can support decision-making process to determine the appropriateness of the business to be run. During this process feasibility calculations that emphasize the financial aspect is still using Microsoft Excel so that data - financial data should be inputted again and again as a result cause problems in the form of clerical errors, duplication of data (Redundancy), inconsistency of data, and data are not integrated. This causes the resulting financial information is not accurate. Inaccuracies in financial information can lead to wrong decisions taken can even lead to business carried stagnated. This study describes about how to determine the feasibility of in manufacturing. Many factors used to determine the feasibility of the business, but this study focuses only on financial factors alone with some financial projections of cost of sales, loss of profits, cash flow and balance sheet. Based on these projections we can see the value of their feasibility using a number of financial parameters of the Payback Period, Average Rate of Return, Profitability Index, Net Pesent Value and Internal Rate of Return. Design tool used to make this decision support system using object-oriented approach. By using the Decision Support System is the potential investors or the management can be easier and faster in receiving information about the feasibility of the business to be run. However, this support system would be more useful if the potential investors or companies already doing business feasibility assessment of aspects of marketing, technical and technology.Keywords: Decision Support System, Payback Periode, Average Rate of Return, Net Present Value, Internal Rate of Return, dan Profitability Index